PERAN PUBLIC RELATIONS DALAM MEMBANGUN CORPORATE IMAGE MELALUI PROGRAM COMMUNITY DEVELOPMENT - Sandra (Jurnal Satya Mandiri Manajemen dan Bisnis, 2016)
in the last decade, company believed their reputation and corporate image is two things that really important for company concern. Their existence is really need the support from public. Corporate sosial programs held in order to strehgthen the sustainability of the campany in a region, by building coopertion among stakeholder by arranging community relation program. For development sosial programs, public relations needs to observe by using the stages in the process for the developing community relations.